Analysis of mathematical literacy ability on PjBL model assisted by observation independent task - Nitasari, Ayu; Suyitno, Hardi; Isnarto, Isnarto (Department of Mathematics, Universitas Negeri Semarang, 2018)
Mathematical literacy ability is an important ability that possessed by students for understanding and solving problems in daily life. In fact, the student’s mathematical literacy ability is still low. Due to that fact, the purpose of this research are (1) to know the learning mastery of mathematical literacy ability on PjBL model assisted by observation independent task; (2) to know the increasing of mathematical literacy ability on PjBL model assisted by observation independent task; and (3) to know the student’s mathematical literacy ability on PjBL model assisted by observation task. This research uses mixed methods with the concurrent embedded model. The population of this research is students of 8th grade in SMP Negeri 29 Semarang academic year 2017/2018. In addition, the sampling technique in quantitative is random technique and the research subject determination is by using certain consideration. Eventually, the results of the research are (1) the mathematical literacy ability on PjBL model assisted by observation independent task achieves learning mastery; (2) there is an increase in mathematical literacy ability on PjBL model assisted by observation independent task; (3) upper group students have excellent mathematical literacy ability, middle group students have good mathematical literacy ability, and lower group students have less mathematical literacy ability.